DEPTH POSITIONING CONTROL OF A SPHERICAL UNDERWATER ROBOT VEHICLE (URV) - JABRALLA, ABDALLA ELTIGANI IBRAHIM (2017)
Underwater Robot Vehicles (URVs) are an underwater system that has its own power and controlled by an onboard computer. URV has been deployed to the numerous duties without human interventions, such as repairing subsea systems and installing networks for scientific research and data collection. In most of these applications, a stable motion is required for the URV. However, the existing URV designs with the fixed ballast tank which generates an internal dynamic for the water inside the tank, leading to the unstable motion for the URV. It hypothesized that an alternative tank mechanism which has variable ballast can perform better and improve the stability of the URV motion. This work focuses on developing a spherical URV has a variable ballast tank mechanism. The complete modeling system of the URV was built and the dimensions and control system components were defined using Simulink!MATLAB and the characteristic of the system was analyzed using the open loop response.